Evaluating the efficacy of recombinant human bone morphogenic protein-2 in the treatment of alveolar clefts with autologous bone grafting using computer-aided engineering techniques. Issue 7 (September 2021) - Liu, B.; Yin, N.B.; Xiao, R.; Li, B.H.; Li, H.D.; Chen, S.X.; Li, S.L.; Wang, Y.Q.
Abstract: Recent studies have indicated the use of recombinant human bone morphogenetic protein-2 (rhBMP-2) to be a viable adjunctive to alveolar cleft reconstruction owing to its osteoinductive capacity. This study aimed to evaluate the efficacy of rhBMP-2 in the treatment of alveolar cleft with autologous bone grafts by precise volumetric analysis. Twenty-six patients (aged 8-14) with unilateral alveolar clefts were enrolled in this comparative study. Patients were divided into two groups: the iliac crest bone graft (ICBG) was placed at the side of the cleft in the control group (ICBG group), and rhBMP-2 was mixed with the ICBG in the rhBMP-2 group (BMP group). Helical computed tomographic images were obtained preoperatively and 12 months postoperatively. The datasets were reconstructed as three-dimensional (3D) images using Mimics software and processed using Geomagic Wrap. The newly formed bone of the alveolar cleft was segmented by identifying the differences between preoperative and postoperative 3D images. In the ICBG group, the volume of newly formed bone ranged from 0.25 to 0.88 cm 3, and the mean (SD) bone formation percentage was 42.01% (15.57%). In the BMP group, the volume of newly formed bone ranged from 0.34 to 1.09 cm 3, and the bone formation mean (SD) percentage was 55.79% (11.84%). There was a statistically significant difference between the two groups in terms of the postoperative percentage of bone formation (p = 0.022). Thus, rhBMP-2 combined with an autologous bone graft is a promising technique to improve the results of secondary alveolar bone grafting.